2010
DOI: 10.1097/yct.0b013e3181cadbf5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Effectiveness and Tolerability of Electroconvulsive Therapy

Abstract: Our data confirm previous studies indicating the good effectiveness of ECT irrespective of age. We also found an excellent tolerability profile in the elderly in our patient sample. There was no mortality, and only transient and no life-threatening adverse events occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 26 publications
3
22
2
3
Order By: Relevance
“…Furthermore, a large age range (23-81 yr) of the present sample including elderly patients has to be acknowledged with a significantly better response to ECT in older patients, which is in line with a multi-site longitudinal study (CORE) showing older age to confer a greater likelihood of achieving remission under ECT (O'Connor et al 2001) and another study reporting even the oldest depressed patients to respond to ECT equally well or even better than younger patients (Tew et al 1999). However, several other studies failed to demonstrate an influence of age on ECT effectiveness (Birkenhäger et al 2010 ;Damm et al 2010). Finally, taking into account the OR usually found by pharmacogenetic studies in major depression, the power of the present study to detect associations with remission is quite low.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, a large age range (23-81 yr) of the present sample including elderly patients has to be acknowledged with a significantly better response to ECT in older patients, which is in line with a multi-site longitudinal study (CORE) showing older age to confer a greater likelihood of achieving remission under ECT (O'Connor et al 2001) and another study reporting even the oldest depressed patients to respond to ECT equally well or even better than younger patients (Tew et al 1999). However, several other studies failed to demonstrate an influence of age on ECT effectiveness (Birkenhäger et al 2010 ;Damm et al 2010). Finally, taking into account the OR usually found by pharmacogenetic studies in major depression, the power of the present study to detect associations with remission is quite low.…”
Section: Discussioncontrasting
confidence: 50%
“…In our cohort, no complaints about being awake before seizure induction were reported by patients. Our data showed that "age" was negatively correlated with all seizure parameters except EEG seizure activity duration, however, ECT is known to be very eff ective for patients of all age groups [ 22 ] . Refi ning our model with age-dependent cut-off s for all parameters, not only with cut-off s for seizure duration and peak heart rate, thus seems necessary.…”
mentioning
confidence: 93%
“…This difference could be because of the differences in the population demographics than the deliberate exclusion of elderly patients from ECT referrals [8]. A study conducted by Damm et al, confirmed the effectiveness of ECT irrespective of age [9]. Though not contraindicated, ECT is not commonly used in extremes of age.…”
Section: Resultsmentioning
confidence: 86%